Exploring key factors related to child well-being: a community-based participatory research together with children with migration background residing in socio-economically disadvantaged areas of Malmö, Sweden - Louise Burenby Yxne; Louise Burenby Yxne; Rathi Ramji; Rathi Ramji; Elisabeth Mangrio; Elisabeth Mangrio; Elisabeth Mangrio; Katarina Sjögren Forss; Katarina Sjögren Forss; Therese Sterner; Therese Sterner; Margareta Rämgård; et al. (Frontiers in Public Health, 2025)
BackgroundChildren with migration background, living in socio-economically disadvantaged areas, are exposed to numerous risk that can negatively affect their well-being. Understanding which key factors build and enable well-being of children with these experiences are therefore essential to support and strengthen their positive development and possibilities to feel well. Studies that include children’s own perspectives and voices in initiatives that concerns them is however scarce, and there is an increased need for participation of children with diverse experiences and life situations in research and knowledge production. Therefore, the aim of this study was to, through a participatory process, explore and enhance the understanding of key factors in the social context that contribute to child well-being among children with a migration background.MethodsThirty-one children, aged 9–12, from three disadvantaged areas in Malmö, Sweden, participated together with researchers in a Community-Based Participatory Research (CBPR) team, exploring factors related to their well-being in their social context. Multi-stage focus groups were held over a year (2023–2024), with different sessions facilitating dialog on the research topic. In total, 49 sessions took place, each on average duration of 1.5 h. The data were analyzed using inductive thematic analysis.ResultsFour main themes, representing key factors related to child well-being, were identified: Enriching Leisure Time, Resourceful Places, Belonging to a Community and Welfare System and Rights. The themes covered structural aspects, such as school, healthcare and human rights, but also more personal dimensions, like close relations and the near environment, related to Bronfenbrenner’s ecological theory of human development.ConclusionThe dialogs with the children provided a deeper understanding and a holistic view of the perceptions of children with migration backgrounds residing in socio-economically disadvantaged areas regarding essential factors for their well-being. Future research should focus on developing strategies that ensure children’s access to the factors they have identified as fundamental to their well-being. Our study has further shown that it is pivotal to ensure children’s inclusion and participation in health promotion initiatives. These initiatives need to be contextually relevant and work toward building community capacity, to promote child well-being.